'Last Drinks at the Hibernian': practice-led research into art and archaeology. Issue 3 (2nd September 2019) - Frederick, Ursula K.; Ireland, Tracy
Abstract: Last Drinks at the Hibernian (Frederick & Ireland 2016) is a collaborative art work that explores what happens when archaeological materials are reconstituted as art and how the 'creative turn' might swivel archaeology's critical lens back onto its own practices and materialities. This creative engagement explores the history and political economy of Australian archaeology, particularly historical archaeology, in order to understand how archaeology is an affective and aesthetic framing of materials, as well as an epistemology for knowledge production about the past from materials in the present. Approaching archaeology as a set of generative practices, 'ways of seeing' and making, we wonder how entangled these sensibilities towards material remains might be and what effect this entanglement has on how heritage is generated, and how the past is represented and remembered through images and things.